Generation of High Quality Memory B Cells - Inoue, Takeshi; Shinnakasu, Ryo; Kurosaki, Tomohiro (Frontiers in Immunology, 2022)
Protection against pathogen re-infection is mediated, in large part, by two humoral cellular compartments, namely, long-lived plasma cells and memory B cells. Recent data have reinforced the importance of memory B cells, particularly in response to re-infection of different viral subtypes or in response with viral escape mutants. In regard to memory B cell generation, considerable advancements have been made in recent years in elucidating its basic mechanism, which seems to well explain why the memory B cells pool can deal with variant viruses. Despite such progress, efforts to develop vaccines that induce broadly protective memory B cells to fight against rapidly mutating pathogens such as influenza virus and HIV have not yet been successful. Here, we discuss recent advances regarding the key signals and factors regulating germinal center-derived memory B cell development and activation, and highlight the challenges for successful vaccine development.